Mental health problems in children with uncomplicated epilepsy; relation with parental anxiety - Gökgöz-Durmaz, Funda; Cihan, Fatma Gökşin; Uzun, Meltem; Kutlu, Ruhuşen (The Turkish Journal of Pediatrics, 2016)
Mental health problems and parental anxiety in children with epilepsy were investigated. Parents of 83 children with epilepsy and 172 healthy children were asked to complete Strengths and Difficulties Questionnaire for their children and State-Trait Anxiety Inventory for themselves. In those with epilepsy, 39.8% (n: 33) were girls, 60.2% (n: 50) were boys and their mean age was 9.34 ± 3.99 years. Control group was more successful in school (p < 0.001). Emotional problems score in children with epilepsy was higher than control group (p < 0.001). Case group's behavior problems and attention deficit hyperactivity scores were higher (p < 0.001, p=0.009 respectively). Prosocial behavior scores of the control group were significantly higher (p=0.004). State (p=0.001) and trait (p=0.001) anxiety levels of parents of children with epilepsy were higher. Children with epilepsy have more neuro-behavioral problems; and their parents have greater anxiety levels. Physicians should be in contact with children with epilepsy for the psychological health of the family besides seizure control.
Keywords: ADHD; behavior problems; epilepsy; parent-child interaction